Evaluating the Social Validity of Project TEAM: A Problem-Solving Intervention to Teach Transition Age Youth with Developmental Disabilities to Resolve Environmental Barriers. Issue 1 (2nd January 2018) - Kramer, Jessica M.; Hwang, I-Ting; Helfrich, Christine A.; Samuel, Preethy S.; Carrellas, Ann
Abstract: Project TEAM teaches transition-age youth with developmental disabilities (DD) to identify physical and social environmental barriers and supports, generate solutions to barriers, and request modifications to increase participation. Establishing the social validity of this environment focused intervention with youth and their parents is critical, given the significant shift the intervention represents from rehabilitation's more traditional focus on body structures and function. University researchers and youth research collaborators conducted a participatory evaluation of the purpose, procedures, and perceived benefits of Project TEAM . Youth with DD ( n = 42) provided feedback using three methods: activity voting, a survey, and a focus group. Parents ( n = 37) also provided feedback. Results suggest that both youth and parents find Project TEAM acceptable and relevant to youth's current and future lives. The majority of youth and parents felt Project TEAM fostered independence and empowerment, although some youth and parents reported challenges with the unique environment-focused approach.